MicroRNAs Bioinformatics Analyses Identifying HDAC Pathway as a Putative Target for Existing Anti‐COVID‐19 Therapeutics - Laura Teodori; Piero Sestili; Valeria Madiai; Sofia Coppari; Daniele Fraternale; Marco Bruno Luigi Rocchi; Seeram Ramakrishna; Maria Cristina Albertini (Frontiers Media S.A., 2020)
Over 313,000 SARS-CoV-2 positive cases have been confirmed in Italy as of 30 September 2020, and the number of deaths exceeding thirty-five thousand makes Italy among the list of most significantly affected countries in the world. Such an enormous occurrence of infections and death raises the urgent demand for effective available treatments. Discovering the cellular/molecular mechanisms of SARS-CoV-2 pathogenicity is of paramount importance to understand how the infection becomes a disease and how to plan any therapeutic approach. In this regard, we performed an in silico analysis to predict the putative virus targets and evidence the already available therapeutics. Literature experimental results identified angiotensin-converting enzyme ACE and Spike proteins particularly involved in COVID-19. Consequently, we investigated the signalling pathways modulated by the two proteins through query miRNet, the platform linking miRNAs, targets, and functions. Our bioinformatics analysis predicted microRNAs (miRs), miR-335-5p and miR-26b-5p, as being modulated by Spike and ACE together with histone deacetylate (HDAC) pathway. Notably, our results identified ACE/ACE2-ATR1-Cholesterol-HDAC axis signals that also matched with some available clinical data. We hypothesize that the current and EMA-approved, SARS-CoV-2 off-label HDAC inhibitors (HDACis) drugs may be repurposed to limit or block host-virus interactions. Moreover, a ranked list of compounds is provided for further evaluation for safety, efficacy, and effectiveness.